2001
DOI: 10.1146/annurev.pharmtox.41.1.203
|View full text |Cite
|
Sign up to set email alerts
|

Novel Effects of Nitric Oxide

Abstract: Nitric oxide (NO), a simple free radical gas, elicits a surprisingly wide range of physiological and pathophysiological effects. NO interacts with soluble guanylate cyclase to evoke many of these effects. However, NO can also interact with molecular oxygen and superoxide radicals to produce reactive nitrogen species that can modify a number of macromolecules including proteins, lipids, and nucleic acids. NO can also interact directly with transition metals. Here, we have reviewed the non--3',5'-cyclic-guanosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
387
0
21

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 533 publications
(411 citation statements)
references
References 209 publications
3
387
0
21
Order By: Relevance
“…in the experiments with continuous excitation should be orders of magnitude lower than in our laser flash photolysis experiments, and thus the hydration of guanine radicals can compete with their combination reactions with superoxide radicals. Biological Implications-In biological systems, superoxide radicals are generated in mitochondria and by neutrophils and macrophages (58). Mitochondria produce superoxide during aerobic respiration, a phenomenon that is significantly enhanced during oxidative stress developed in response to various diseases.…”
Section: Combination Of G(ϫh) ⅐ and O 2 Radicals; Electron Transfermentioning
confidence: 99%
“…in the experiments with continuous excitation should be orders of magnitude lower than in our laser flash photolysis experiments, and thus the hydration of guanine radicals can compete with their combination reactions with superoxide radicals. Biological Implications-In biological systems, superoxide radicals are generated in mitochondria and by neutrophils and macrophages (58). Mitochondria produce superoxide during aerobic respiration, a phenomenon that is significantly enhanced during oxidative stress developed in response to various diseases.…”
Section: Combination Of G(ϫh) ⅐ and O 2 Radicals; Electron Transfermentioning
confidence: 99%
“…This chemistry has been studied extensively because of the dietary and environmental exposure of humans to these substances [3][4][5]. Toxicological studies of deamination became more significant when it was recognized that endogenous nitric oxide [6,7] causes nitrosation [8,9], and that this process is accelerated by chronic inflammatory diseases [10,11]. It has been known for a long time that deamination of adenine 1, guanine 2, and cytosine 3 (Scheme 1) results in the formation of hypoxanthine, xanthine, and uracil, respectively, and these products are thought to result from DNA base diazonium ions 4-6, respectively, by direct nucleophilic dediazoniation.…”
mentioning
confidence: 99%
“…Although many effects of NO are mediated through its direct interaction with guanylyl cyclase activation (1)(2)(3)(4)(5)(6)(7)(8), its indirect action via secondary reactions with reactive oxygen species, forming reactive nitrogen species accounts for other effects. The reaction of NO and its reactive intermediates with protein bound tyrosine residues causes nitrotyrosine formation (9). Several mechanisms for nitrotyrosine formation have been suggested that involve peroxynitrite or myeloperoxidase (10).…”
mentioning
confidence: 99%